Identifikasi Tumbuhan Obat Tradisional Berbasis Kearifan Lokal di Desa Ranggagata Kecamatan Praya Barat Daya Kabupaten Lombok Tengah - Emi Sundari; Baiq Muli Harisanti; Siti Nurhidayati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Medicinal plants are all plants that can be used as medicine, ranging from those visible to the eye to those visible under a microscope. The medicinal plants referred to in this study are medicinal plants whose parts, whether roots, stems, leaves, flowers or tubers, are used as ingredients for ingredients derived from plants that have been used for generations for treatment based on local knowledge and understanding. Local wisdom is the values of humanity, togetherness, brotherhood, and knowledge which are considered important enough to be preserved, one of which is regarding medicinal plants used by the community. This research is a descriptive explorative research. This research is to reveal information about the types of traditional medicinal plants in Ranggagata Village, Praya Barat Daya District, Central Lombok Regency using the snowball sampling method. The data was collected through observation, interviews with non-medical healers (purchases), and documentation. The results showed that there were 41 types of medicinal plants from 32 families which were successfully identified and used by the people of Ranggagata Village, Praya Barat Daya District, Central Lombok Regency.